Coating biopolymer nanofibers with carbon nanotubes accelerates tissue healing and bone regeneration through orchestrated cell- and tissue-regulatory responses. (May 2020) - Patel, Kapil D.; Kim, Tae-Hyun; Mandakhbayar, Nandin; Singh, Rajendra K.; Jang, Jun-Hyeog; Lee, Jung-Hwan; Kim, Hae-Won
ABSTRACT: Tailoring the surface of biomaterial scaffolds has been a key strategy to modulate the cellular interactions that are helpful for tissue healing process. In particular, nanotopological surfaces have been demonstrated to regulate diverse behaviors of stem cells, such as initial adhesion, spreading and lineage specification. Here, we tailor the surface of biopolymer nanofibers with carbon nanotubes (CNTs) to create a unique bi-modal nanoscale topography (500 nm nanofiber with 25 nm nanotubes) and report the performance in modulating diverse in vivo responses including inflammation, angiogenesis, and bone regeneration. When administered to a rat subcutaneous site, the CNT-coated nanofiber exhibited significantly reduced inflammatory signs (down-regulated pro-inflammatory cytokines and macrophages gathering). Moreover, the CNT-coated nanofibers showed substantially promoted angiogenic responses, with enhanced neoblood vessel formation and angiogenic marker expression. Such stimulated tissue healing events by the CNT interfacing were evidenced in a calvarium bone defect model. The in vivo bone regeneration of the CNT- coated nanofibers was significantly accelerated, with higher bone mineral density and up-regulated osteogenic signs (OPN, OCN, BMP2) of in vivo bone forming cells. The in vitro studies using MSCs could demonstrate accelerated adhesion and osteogenic differentiation and mineralization, supporting the osteo-promoting mechanism behind the in vivo bone forming event. These findings highlight that the CNTs interfacing of biopolymer nanofibers is highly effective in reducing inflammation, promoting angiogenesis, and driving adhesion and osteogenesis of MSCs, which eventually orchestrate to accelerate tissue healing and bone regeneration process. Statement of significance: Here we demonstrate that the interfacing of biopolymer nanofibers with carbon nanotubes (CNTs) could modulate multiple interactions of cells and tissues that are ultimately helpful for the tissue healing and bone regeneration process. The CNT-coated scaffolds significantly reduced the pro-inflammatory signals while stimulating the angiogenic marker expressions. Furthermore, the CNT-coated scaffolds increased the bone matrix production of bone forming cells in vivo as well as accelerated the adhesion and osteogenic differentiation of MSCs in vitro . These collective findings highlight that the CNTs coated on the biopolymer nanofibers allow the creation of a promising platform for nanoscale engineering of biomaterial surface that can favor tissue healing and bone regeneration process, through a series of orchestrated events in anti-inflammation, pro-angiogenesis, and stem cell stimulation. Graphical abstract: Image, graphical abstract